1994
DOI: 10.18174/njas.v42i1.615
|View full text |Cite
|
Sign up to set email alerts
|

Between-animal variation in biological efficiency as related to residual feed consumption

Abstract: Production levels in livestock (cattle, pigs and poultry) have been increased considerably, with a correlated increase in gross feed efficiency. However, mature body weight has also increased, leading to higher maintenance costs. Thus, net feed efficiency has been little improved. Breeding for lower body weight has not been successful, but there are possibilities for reduction of feed consumption independent of production and body weight (residual feed consumption). It is as yet uncertain to what extent animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 0 publications
2
12
0
2
Order By: Relevance
“…The discrepancy between both sets of results could be related to the higher susceptibility to heat stress of lactating sows than growing pigs and also to the high relative humidity in the present study. This apparent higher susceptibility of RFI ─ sows to the TROP climate, as expressed by the reduction of appetite, is in agreement with the hypothesis that an animal with a low RFI could have fewer possibilities to cope with stress (Luiting et al, 1994). From that, it can be hypothesized that the energetic requirements for sustaining body temperature in hot conditions would exceed the residual part of energy intake in RFI ─ sows, leading to enhanced decline in heat production and ADFI.…”
Section: Impact Of Divergent Selection For Rfi On Performance Of Sowssupporting
confidence: 84%
“…The discrepancy between both sets of results could be related to the higher susceptibility to heat stress of lactating sows than growing pigs and also to the high relative humidity in the present study. This apparent higher susceptibility of RFI ─ sows to the TROP climate, as expressed by the reduction of appetite, is in agreement with the hypothesis that an animal with a low RFI could have fewer possibilities to cope with stress (Luiting et al, 1994). From that, it can be hypothesized that the energetic requirements for sustaining body temperature in hot conditions would exceed the residual part of energy intake in RFI ─ sows, leading to enhanced decline in heat production and ADFI.…”
Section: Impact Of Divergent Selection For Rfi On Performance Of Sowssupporting
confidence: 84%
“…Calculated as the sum of fasting heat production and retained energy (Noblet et al, 1994); the latter is obtained as the difference between ME and total heat production. and broilers (Luiting et al, 1994;Carré et al, 2008) and in pigs (de Haer et al, 1993;present study). Differences in metabolism are assumed to be the major factor contributing to differences in feed efficiency.…”
mentioning
confidence: 88%
“…Studies have shown that the lower energy losses as methane during digestion (Nkrumah et al, 2006) and greater energy retention as protein (Basarab et al, 2003) may also contribute to the better efficiency of feed use in low-RFI cattle. Other factors such as physical activity (Barea et al, 2010;Luiting et al, 1994) and responsiveness to stress (Knott et al, 2008; can also be linked to FE due to their impact on metabolic rate and, consequently, on the requirements of energy for maintenance.…”
Section: Introductionmentioning
confidence: 99%